A rare incident of intraoral formalin injection - Sulu, Sumana; Maharjan, Iccha kumar; Regmee, Pragya; Adhakari, Sagar; Luitel, Abhinaya; Khatiwada, Kripa (Birat Journal of Health Sciences, 2023)
Formalin is a hazardous chemical that needs careful handling and special storage. It is generally used in dentistry because of its disinfectant and fixative properties. Negligence on part of the dental professionals by accidentally injecting formalin rather than the original anesthetic can lead to internal tissue damage and also may induce a life threatening situation. The general practice of storing formalin in the original anesthetic bottles and being supported by untrained assistants is the most common reason for this mishap to happen. The operating dentist should be careful and apprehensive of the medicines and chemicals available in the operatory and re-check the solution being injected in the case as to not land up in complications because of the negligence. Successful management can be done by cautious debridement and empirical medicine therapy.